2023
DOI: 10.1371/journal.pbio.3001888
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient CRISPR-mediated gene editing in a rotifer

Abstract: Rotifers have been studied in the laboratory and field for over 100 years in investigations of microevolution, ecological dynamics, and ecotoxicology. In recent years, rotifers have emerged as a model system for modern studies of the molecular mechanisms of genome evolution, development, DNA repair, aging, life history strategy, and desiccation tolerance. However, a lack of gene editing tools and transgenic strains has limited the ability to link genotype to phenotype and dissect molecular mechanisms. To facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…As a prevalent group of zooplankton, rotifers have been well studied in microevolution, ecodynamics and ecotoxicology for over 100 years. Like water fleas, rotifers have a unique way of reproduction [ 235 ]. Yet the lack of gene-editing tools and transgenic strains has limited the ability to link genotypes to phenotypes and dissect molecular mechanisms.…”
Section: Crispr/cas In Marine Zooplankton Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…As a prevalent group of zooplankton, rotifers have been well studied in microevolution, ecodynamics and ecotoxicology for over 100 years. Like water fleas, rotifers have a unique way of reproduction [ 235 ]. Yet the lack of gene-editing tools and transgenic strains has limited the ability to link genotypes to phenotypes and dissect molecular mechanisms.…”
Section: Crispr/cas In Marine Zooplankton Researchmentioning
confidence: 99%
“…Yet the lack of gene-editing tools and transgenic strains has limited the ability to link genotypes to phenotypes and dissect molecular mechanisms. A recent study reported that CRISPR-mediated gene editing can effectively address the gap in the research [ 235 ]. MutL is a mismatch repair protein that plays a crucial role in meiosis in sexual organisms, and mlh3 gene is a homologue of the MutL gene [ 235 ].…”
Section: Crispr/cas In Marine Zooplankton Researchmentioning
confidence: 99%
See 1 more Smart Citation